2018
DOI: 10.1007/s10826-018-1261-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Child Maltreatment, Harsh Parenting, and Sleep with Adolescent Mental Health

Abstract: Youth who suffer from psychiatric disorders are at high risk for negative outcomes, including aggression and substance abuse. Although many youth with psychiatric disorders have endured harsh parenting and/or child maltreatment (CM), differential associations between these experiential factors have yet to be fully explored. Sleep problems have also been implicated in psychiatric disorders and are consistently associated with CM. The overlap and unique contributions of CM and sleep problems to the mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 82 publications
0
22
0
1
Order By: Relevance
“…Third, our findings may contribute to the broader literature on the importance of spillover of marital relationships. For decades, scholars have noted that problematic parenting is linked to poorer development for children (Calhoun et al, 2019;Stroud et al, 2015;Warmuth et al, 2020). A growing body of work documents that spillover may be part of the reason for this association (Chung et al, 2009;Kaczynski et al, 2006;Warmuth et al, 2020).…”
Section: The Role Of Family Spillovermentioning
confidence: 99%
“…Third, our findings may contribute to the broader literature on the importance of spillover of marital relationships. For decades, scholars have noted that problematic parenting is linked to poorer development for children (Calhoun et al, 2019;Stroud et al, 2015;Warmuth et al, 2020). A growing body of work documents that spillover may be part of the reason for this association (Chung et al, 2009;Kaczynski et al, 2006;Warmuth et al, 2020).…”
Section: The Role Of Family Spillovermentioning
confidence: 99%
“…The development of anxiety disorders due to parent-child maltreatment can be understood from previous research detailing how continuous and frequent exposure to child maltreatment interrupts hypothalamic-pituitary-adrenal axis functioning and leads to neurobiochemical changes in the brain [25]. These changes include, an increase in thalamic grey matter volumes of the subcortical region of the brain which can result in the development of GAD symptoms [26,27]. Moreover, parents' constant maltreatment can disrupt an adolescent's sense of safety resulting in various fears, apprehensions, cognitive deficits, and emotional vulnerability, leading to anxiety disorders [28].…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated a 25.5% of physical abuse and a 17.9% of emotional abuse by parents among Pakistani Children (Ali & Khuwaja, 2014). Literature indicated that continuous and frequent exposure to child maltreatment interrupts hypothalamic pituitary adrenxal axis functioning and leads to neurobiochemical changes in brain including an increase in thalamic grey matter volumes of subcortical region of the brain which can result in development of GAD symptoms (Calhoun, Ridenour, & Fishbein, 2019;Liao et al, 2013). Moreover, constant maltreatment by parents can disrupt the safety blanket of an adolescent resulting in various fears, apprehensions, cognitive de cit and emotional vulnerability which could lead to anxiety disorders (Berzenski, Madden, & Yates, 2019).…”
Section: Introductionmentioning
confidence: 99%